SCIENTIFIC AND PUBLICISTIC STYLES OF SPEECH, ITS LINGUISTIC AND STRUCTURAL FEATURES - Suerbasova, Zh.M. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
Scientific style is one of the book styles that is used in scientific works, textbooks, educational and reference literature, and in speeches on scientific topics. Science is a sphere of human activity, one of the forms of social consciousness. The concept of "science" includes both the activity of obtaining new knowledge (research, study), and the result of this activity – the sum of scientific knowledge obtained, forming a scientific picture of the world. Publicistic style has a special place in the style of literary language, because in many cases it incorporates information already reflected in the scientific or official-business style. Using the information from the fields of science journalism focuses on the intellectual reflection of reality, and texts created in the framework of legislation, suggested the socio-political, civil tone. The article is devoted to the study of scientific and journalistic styles.
Keywords: Scientific style; Journalistic style; linguistic features; structural features; media; scientific articles